Freemasonry in Colombia (18th-19th centuries): French or continental origin, leading Freemasons, the Catholic Church, political parties and revolutionary elements in South America - Arrieta-López, Milton (Perseitas, 2020)
The history of Colombian Freemasonry can be divided into three clearly identifiable stages, this work focused on the first historical stage characterized by the influence of continental European Freemasonry. This article analyzed the essence of French freemasonry on the origin of the Colombian nation-state. The impact of operative or patriotic lodges in South America was reviewed in general, as well as the relations between the Catholic Church and the 19th-century leading freemasons. The methodology used is documentary review, bibliographic and critical analysis when consulting, reviewing and analyzing reference sources. The article attempts to gauge the scope of the masonic influence on the process of independence from Spain, and it arrives at the conclusion that without the intervention of masonic elements the revolutionary goals would not have materialized in the way they did.